Udział Wojska Polskiego w misjach stabilizacyjnych w krajach byłej Jugosławii - Hudyma, Przemysław (Studia Europaea Gnesnensia, 2010)
In a synthetic manner, the author presents participation of Polish soldiers in peace mission in the Balkans. The timeline and the concept of the article have been designed to demonstrate the role of the missions in Polish bid for NATO membership. In this perspective, the missions served Polish Armed Forces as a source of necessary experience and knowledge of NATO procedures